A handbook of Marxism : being a collection of extracts from the writings of Marse, Engels... / the passages being chosen by Emile Burns... - Burns, EmileMarx, Karl (1818-1883) Engels, Friedrich (1820-1895) Lenin, Vladimir Il'ich (1870-1924) Stalin, Iossiv Vissarionovich (1879-1953)
Incluye glosari de nombres e índice.